Spontaneous Intracerebral Hemorrhage: Computed Tomographic Characteristics and Outcome - Aimara de la Caridad Vergara Santos; José Luis Rodríguez Monteagudo; Pedro Barrós Fuentes; Rubén Sánchez Abdala; Osmani Quintero Martínez (Revista Finlay, 2015)
Background: strokes are the third leading cause of death among adults and 10-15 % of them are due to spontaneous intracerebral hemorrhage. Objective: to characterize spontaneous intracerebral hemorrhage through computed tomography scan and its outcome. Methods: a case series study was conducted comprising patients diagnosed with spontaneous intracerebral hemorrhage admitted to the Arnaldo Milián Castro Provincial University Hospital in Villa Clara from January 2009 to January 2010. Tomographic variables of interest were derived from evaluation of spontaneous intracerebral hematomas. Results: fifty-nine cases of spontaneous intracerebral hemorrhage were studied, 23 were located in lobar regions, 4 had severe midline shift, and 2 showed volume greater than 80 ml. Eight out of eleven with extension into the ventricular system had an unfavorable outcome. Among those with thalamic hemorrhage, patients with diameter larger than 4cm and extension into the ventricular system died. Patients with putaminal hemorrhage larger than 4 cm and posterior fossa hematoma with hydrocephalus had a poor outcome, as well as most individuals (55) with other mass effects. Most lobar hematomas (14 out of 23) had a satisfactory outcome, unlike cerebellar and brainstem hematomas. Conclusions: tomographic variables that had a negative impact on the outcome were: volume greater than 80 ml, severe midline shift, diameter larger than 4 cm, extension into the ventricular system, hydrocephalus, other signs of mass effect and brainstem location.